Pembinaan Masyarakat Pesisir dan Nelayan Kecamatan Sape Kabupaten Bima - Wawan Mulyawan (BADAN PENERBIT STIEPARI PRESS, 2022)
The marine and fisheries subsector is one of the development subsectors based on natural resources and environmental services. The strength of this sector, contained in its economic potential, should be optimized to become a pillar of the nation's competitive advantage in economic development and people's prosperity. Fishermen, fishing activities, and managing marine resources, are not only routine activities with the sole focus on the family economy, but are also placed as a whole that gives meaning to life and life at large. In this framework, fishermen place their fishing activities in the context of their cultural values. Fishermen's knowledge is accumulated in history and experience through the process of socialization, activities and roles of stewardship that are inherited or transferred to the next generation. The marine and fisheries subsector is one of the development subsectors based on natural resources and environmental services.